Scolacium w Kalabrii – wybrane źródła literackie do poznania historii miasta - Grzelak-Krzymianowska, Adriana (Collectanea Philologica, 2014)
Calabria is a region where we may find many traces of very old settlements and the development of human civilization, because it was already inhabited during the Paleolithic Era. Its later, over two thousand years history is characterized by the influence of such ethno-cultural groups as the Greeks, the Brutti, the Romans, the Byzantines, the Saracens and the Normans. Hence, Calabria has become an infinite source of fascination for all who seek the remains of ancient times in Italy. The purpose of my article is to present the history of Scolacium – one of the ancient towns in the Italian province of Calabria basing, above all, on selected literary evidence on the issue. My studies concentrate mainly on pointing out the numerous references and allusions to its name and on the analysis of longer or shorter depictions of the town found in various Greek and Roman literary works and their application in a chronological reconstruction of the town’s past events as an example of historical processes observed on the territory of Magna Graecia.